A Critical Criminological Analysis of the Reformulation of Criminal Offences in the Indonesian Criminal Code - Hasdiwanti Ha; Muhammad Ikram Nur Fuady (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This study aims to analyze the reformulation of criminal offenses in the Indonesian Criminal Code (KUHP) through the perspective of critical criminology. Existing studies on the new Criminal Code have primarily focused on normative legal issues, while analyses of criminalization and social control remain limited. The novelty of this study lies in applying critical criminology to examine the reformulation of criminal offenses not merely as a legislative reform, but also as a social process that shapes the construction of crime. This research employs a normative legal research method using statutory and conceptual approaches to examine the provisions concerning morality offenses, insults against the President and the government, defamation, and restrictions on freedom of expression under Law No. 1 of 2023 on the Indonesian Criminal Code. Legal materials were collected through library research and analyzed using qualitative methods. The findings demonstrate that the reformulation of offenses in the new Criminal Code does not entirely reflect a neutral legal reform; rather, it represents a process of criminalization shaped by power relations, dominant moral values, and mechanisms of social control. Such conditions may result in restrictions on civil liberties and selective law enforcement if the relevant provisions are not interpreted and applied proportionately. This study underscores the importance of implementing the new Criminal Code in a manner that upholds human rights and substantive justice, while contributing to the development of criminal law scholarship by advancing critical criminology as an alternative analytical framework for evaluating criminal policy in Indonesia